A ROBUST AUTONOMOUS VEHICULAR NAVIGATION SYSTEM USING RIMU-BASED INS/GNSS INTEGRATED SCHEME - K.-W. Chiang; C.-H. Huang; Y.-T. Chiu; T.-C. Wu; S. Tsai; K.-Y. Lin (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
The application of the INS/GNSS integrated system is widespread in vehicle navigation. However, in certain complex urban areas, achieving accurate positioning for autonomous vehicles at level 3 and beyond presents a challenge. Moreover, ensuring the continuous availability of the navigation system is crucial for maintaining vehicle safety under all circumstances. Consequently, the specifications of the Inertial Measurement Unit (IMU), which have a direct correlation with cost, dominate the performance of the navigation system in environments where GNSS signals are denied or challenging. To implement level 3 autonomous vehicles, a strategy based on redundant IMUs (RIMU) is employed to not only enhance accuracy and availability but reduce the overall cost of the navigation system. This research mainly focuses on the development of a robust autonomous vehicular navigation system by designing an integrated algorithm for the low-cost RIMU and GNSS receiver within the INS/GNSS integration scheme. The positioning performance is analyzed by using a reference system and a benchmark system in the open sky, GNSS challenging, and GNSS outage scenarios.